CMRF-56+ blood dendritic cells loaded with mRNA induce effective antigen-specific cytotoxic T-lymphocyte responses. (2nd June 2016) - Fromm, Phillip D.; Papadimitrious, Michael S.; Hsu, Jennifer L.; Van Kooten Losio, Nicolas; Verma, Nirupama D.; Lo, Tsun Ho; Silveira, Pablo A.; Bryant, Christian E.; Turtle, Cameron J.; Prue, Rebecca L.; Vukovic, Peter; Munster, David J.; et al.
ABSTRACT: There are numerous transcriptional, proteomic and functional differences between monocyte-derived dendritic cells (Mo-DC) and primary blood dendritic cells (BDC). The CMRF-56 monoclonal antibody (mAb) recognizes a cell surface marker, which is upregulated on BDC following overnight culture. Given its unique ability to select a heterogeneous population of BDC, we engineered a human chimeric (h)CMRF-56 IgG4 mAb to isolate primary BDC for potential therapeutic vaccination. The ability to select multiple primary BDC subsets from patients and load them with in vitro transcribed (IVT) mRNA encoding tumor antigen might circumvent the issues limiting the efficacy of Mo-DC. After optimizing and validating the purification of hCMRF-56 + BDC, we showed that transfection of hCMRF-56 + BDC with mRNA resulted in efficient mRNA translation and antigen presentation by myeloid BDC subsets, while preserving superior DC functions compared to Mo-DC. Immune selected and transfected hCMRF-56 + BDC migrated very efficiently in vitro and as effectively as cytokine matured Mo-DC in vivo . Compared to Mo-DC, hCMRF-56 + BDC transfected with influenza matrix protein M1 displayed superior MHC peptide presentation and generated potent antigen specific CD8 + T-cell recall responses, while Wilms tumor 1 (WT1) transfected CMRF-56 + BDC generated effective primary autologous cytotoxic T-cell responses. The ability of the combined DC subsets within hCMRF-56 + BDC to present mRNA delivered tumor antigens merits phase I evaluation as a reproducible generic platform for the next generation of active DC immune therapies.